Results of levator-advancement blepharoptosis repair using a standard protocol: effect of epinephrine-induced eyelid position change. - Bartley, G B (1996)
PURPOSE: Blepharoptosis repair by levator advancement is successful in most instances, but the postoperative eyelid level is not uniformly predictable. This study was undertaken to evaluate the possible effect of epinephrine (from local anesthetic) on eyelid position. METHODS: Seventeen adults with acquired unilateral ptosis as a result of levator aponeurosis dehiscence underwent levator aponeurosis advancement. The distance between the upper eyelid margin and the central corneal light reflex was measured preoperatively with the patient in both the upright and the supine position, 10 minutes after injection of 1.0 mL of anesthetic solution (2% lidocaine with 1:100,000 epinephrine and 12 U hyaluronidase per mL) in the supine position, intraoperatively after skin closure in the supine position, and 1 week or more postoperatively in the upright position. The ptotic lid was positioned intraoperatively in relation to the contralateral unoperated lid according to the change (presumably) induced by epinephrine stimulation of Müller's muscle. RESULTS: Eleven (65%) of the 17 patients had final postoperative lid positions within 1 mm between eyes. Two patients (12%) had undercorrection. Four patients (24%) had overcorrection by > 1 mm. The overcorrected lids were satisfactorily positioned, however, and none required further surgery; in 3 of these 4 patients, the unoperated lid had become ptotic, probably as a result of Hering's law. Differences between operated and unoperated lids and between the different times of measurement were analyzed. Significant changes in lid position occurred in the ptotic lids after injection (mean, +1.1 +/- 1.5 mm; median, +1.0 mm; P = .004) and in the final intraoperative difference between operated and unoperated lids (mean, +0.8 +/- 0.9 mm; median, +1.0 mm; P = .003). The change in the unoperated lid from preoperative upright to preoperative supine was significantly greater in the 6 failures (mean, -0.8 +/- 0.6 mm; median, -1.0 mm) than in the 11 successful outcomes (mean, +0.1 +/- 0.8 mm; median, 0.0 mm; P = .03). The change in unoperated lid position after injection of the ptotic lid was significantly greater in the failures (mean, +0.4 +/- 0.5 mm; median, +0.3 mm) than in the successful cases (mean, -0.2 +/- 0.4 mm; median, 0.0 mm; P = .02). CONCLUSION: Although it seems intuitively reasonable and clinically appropriate to account for the stimulatory effect of epinephrine during ptosis surgery, such intraoperative compensation alone did not yield a universally successful outcome in this study.